Association of sex hormone-binding globulin and free testosterone with mortality in men with type 2 diabetes mellitus. Issue 1 (January 2016) - Tint, Aye N; Hoermann, Rudolf; Wong, Henry; Ekinci, Elif I; MacIsaac, Richard J; Jerums, George; Zajac, Jeffrey D; Grossmann, Mathis
Abstract : Objective: Low circulating testosterone levels have been associated with increased mortality in men. We hypothesized that the prognostic role of testosterone in men with type 2 diabetes mellitus (T2DM) is influenced by its carrier protein sex hormone-binding globulin (SHBG). Design: We conducted a prospective cohort study at a tertiary referral centre. Methods: In total, 531 men with T2DM presenting to a diabetes clinic in 2004–2005 were followed prospectively until death, or July 31, 2014, and a survival analysis was performed. The main outcome measure was all cause mortality. Results: Over a mean (s.d. ) follow up of 7.6 years (2.6) 175 men (33%) died. In Cox proportional hazard models both higher SHBG (Hazard Ratio (HR) 1.012 (95% CI 1.002–1.022), P =0.02) and lower calculated free testosterone (cFT) (HR 0.995 (95% CI 0.993–0.998), P =0.001) were risk factors for all cause mortality independently of age, BMI, presence of macro- and microvascular disease, duration of T2DM, hemoglobin, renal function, insulin use, C-reactive protein and homeostatic model of insulin resistance. By contrast, the inverse association of total testosterone (TT) with mortality weakened after these adjustments ( P =0.11). SHBG remained associated with mortality ( P <0.001) both if substituted for or added to TT in the multivariable model. In the fully adjusted model, an increase of SHBG by 17.3 nmol/l (1s.d. ) increased mortality by 22% and a decrease in cFT by 81 pmol/l (1s.d. ) increased mortality by 45%. Conclusions: The association of SHBG with mortality in men with T2DM is novel. Whether SHBG acts via regulation of testosterone, has intrinsic biological roles, or is a marker of poor health requires further study.